University-Enterprise as Educational Space for Students. An Experience in ProCal-ProSer Project - Dávila, A.D.; Melendez, K.; Pessôa, M.S.P. (Institute of Electrical and Electronics Engineers, 2019)
The engineering professional education is a constant concern of the faculties and it has been the basis for various efforts (research, development and innovation) to meet high levels of excellence. In this context, the student outcomes, as defined by the ICACIT (an accreditation agency), establish a set of expected characteristics (which are measured) at the end of engineering education, what demands new educational spaces to achieve them. The aim of this study is to present the experience within the ProCal-ProSer project, a process improvement program developed in small software development enterprises, as an educational space that contributes to the student outcomes. For this article an analysis of the student outcomes was performed, based on the experiences within the Project. The students, in partnership with enterprise, completed a cycle of process improvement and presented this experience as their final projects. The experiences developed allow stablish that the Project became a good educational space and it contributed in the consolidation of 11 student outcomes (from 12 defined by ICACIT).
Keywords: General partnership; Accreditation; Space (punctuation); Context (archaeology); Excellence; Process (computing); Consolidation (business); Engineering management; Engineering education; Knowledge management; Engineering; Computer science; Medical education; Business; Political science; Medicine; https://purl.org/pe-repo/ocde/ford#2.11.04